2022
DOI: 10.1093/cid/ciac802
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Selection of Sotrovimab Escape Variants in Severe Acute Respiratory Syndrome Coronavirus 2 Omicron-Infected Immunocompromised Patients

Abstract: Background Monoclonal antibodies (mAb) targeting SARS-CoV-2 are predominantly less effective against Omicron variants. Immunocompromised patients often experience prolonged viral shedding and are therefore at increased risk for viral escape mutations, when mAbs are used as monotherapy. Methods In an observational, prospective cohort, 57 patients infected with Omicron variants receiving sotrovimab alone or in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
6
34
0
Order By: Relevance
“…Whole viral genome sequencing revealed Spike mutations (L5F, Y145D, E340A, L582F, F855L, and L938F) after receiving sotrovimab, as shown in Supplementary Table 2 (GISAID accession EPI_ISL_16849243, EPI_ISL_16849243, EPI_ISL_16849245). Notably, S:E340A confers immune escape to sotrovimab [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . We also observed an overall reduction in the number of S epitopes that could be presented by the patient's HLA alleles, as depicted in Supplementary Materials.…”
Section: Dear Editormentioning
confidence: 99%
“…Whole viral genome sequencing revealed Spike mutations (L5F, Y145D, E340A, L582F, F855L, and L938F) after receiving sotrovimab, as shown in Supplementary Table 2 (GISAID accession EPI_ISL_16849243, EPI_ISL_16849243, EPI_ISL_16849245). Notably, S:E340A confers immune escape to sotrovimab [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . We also observed an overall reduction in the number of S epitopes that could be presented by the patient's HLA alleles, as depicted in Supplementary Materials.…”
Section: Dear Editormentioning
confidence: 99%
“…In vitro studies, however, demonstrated that sotrovimab had lost activity against the BA.2 strain almost completely [ 90 ]. Even worse, it has been demonstrated that in immunocompromised patients undergoing treatment with sotrovimab, treatment failure was associated with emerging spike mutations conferring resistance to sotrovimab [ 115 ]. On the other hand, two case reports suggested that the use of sotrovimab as an adjunctive to remdesivir therapy in severely immunocompromised AIDS patients showed a dramatic improvement in symptoms and rapid viral clearance [ 116 , 117 ].…”
Section: Management Of Covid-19 In Pwhmentioning
confidence: 99%
“… Green, orange and red indicate no, mild/moderate, and severe reduction in potency in vitro. Data composition as per [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. …”
Section: Figurementioning
confidence: 99%
“…At the moment, genomic epidemiology has identified Omicron as the only variant of concern. In this context, the susceptibility of circulating SARS-CoV-2 variants i.e., Omicron BA.2, BA.4, BA.5, and its subvariants, i.e., BA.2.75.2, BA.4.6, and BQ.1.1, against anti-SARS-CoV-2 antibodies remains variable [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] (see Table 1 ). Sotrovimab [ 14 , 15 , 16 , 17 ], Casirivimab/Imdevimab [ 18 ], and Bamlanivimab/Etesevimab [ 18 , 19 ], although effective against the previous variants, i.e., alpha (B.1.1.7), beta (B.1.351), gamma (P.1), delta (B.1.617.2, non-AY.1/AY.2), and Omicron (B.1.1.529/BA.1 and BA.1.1), they seem to be inactive against the present ones (BA.2, BA.4, BA.5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation